THE CONCEPT OF A DIGITAL CAREER GUIDANCE SYSTEM IN IT: ARCHITECTURE, FUNCTIONALITY, AND APPLICATION SCENARIOS - Sliusarchyk, Denys (Public Management and Policy, 2025)
This article explores the concept of creating an information system for digital career guidance, specifically tailored to the field of information technology. The relevance of the study is driven by the rapid transformation of the IT market, the complexity of navigating career directions, and the limited effectiveness of existing tools that support youth in choosing a profession. The aim is to develop the architecture of a digital platform that combines the classification of IT professions, a competency-based approach, and algorithms for personalized recommendations. Methodologically, the system is based on a modular design with four key components: an adaptive user questionnaire, an analytical core, a knowledge base, and a visual interface for navigating professional trajectories. The article analyzes the limitations of international platforms (O*NET, ESCO, CareerExplorer) in the context of IT specializations, the lack of integration with educational trajectories, and the absence of personalized algorithms. The proposed system enables the construction of individual learning paths, provides career and training recommendations, and can be integrated with LMS platforms such as Moodle and Canvas. The results section describes scenarios for applying the system in schools, colleges, career centers, and municipal youth programs. The platform can be adapted to different user needs and scaled to other sectors, including STEM, design, and green energy. The system introduced in this research offers a valuable approach to digitally transforming career guidance and competency enhancement within the IT sector, tailored to meet the demands of society, education, and the knowledge-based economy. The practical significance of the project lies in the development of a tool that can strengthen digital career guidance in Ukraine and support the growth of next-generation educational ecosystems.